Variabilitas Spasial Makrozoobenthos di Zona Pesisir Tropis: Studi Kasus dari Pantai Kastela, Ternate, Indonesia - Syukur, Rinaldo; Juniartin, Juniartin; Muna, Lintal (Alpatih Harapan Semesta, 2024)
Kastela Beach, located in Kastela Village, Ternate Island District, Ternate City, North Maluku, has main characteristics such as stretches of fine alluvial sand and an ecosystem of seagrass beds and coral reefs extending over 2 km. This research aims to identify the types of macrozoobenthos, study their distribution and abundance, and analyze the factors affecting them along the coast of Kastela Beach. The research was conducted using qualitative methods with an observational approach and quadrat analysis. The data analysis technique used the species abundance index according to the Ludwig and Reynold formulation. The research results revealed the presence of six macrozoobenthic species evenly distributed across five plots: Holothuria atra (21 individuals), Diadema setosum (30 individuals), Tridacna gigas (9 individuals), Conus marmoreus (11 individuals), Strombus sp (22 individuals), and Pinctada margaritifera (5 individuals). Factors of physicochemical environment, such as brightness, water temperature, salinity, and local community activities, were found to play an important role in influencing the abundance of macrozoobenthos.